2003
DOI: 10.2174/0929867033457133
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Target of Antioxidative Therapy for Diabetic Vascular Complications-Vascular NAD(P)H Oxidase

Abstract: A growing body of evidence has shown that oxidative stress may be involved in the development of vascular complications associated with diabetes. However, the molecular mechanism for increased reactive oxygen species (ROS) production in diabetes remains uncertain. Among various possible mechanisms, attention have increasingly been paid to NAD(P)H oxidase as the most important source of ROS production in vascular cells. High glucose level stimulates ROS production through protein kinase C (PKC)-dependent activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Diabetes and high glucose conditions can increase the formation of ROS by multiple biochemical pathways, including glucose auto-oxidation, activation of the polyol pathway which can decrease levels of reduced glutathione and/or increase advanced glycation end products and activation of PKC which activates NAD(P)H oxidase (Fig. 10) (Brownlee, 2001;Brownlee, 2005;Inoguchi et al, 2003a;Inoguchi et al, 2003b;Jain, 2006). All of these events have been suggested to be initiated by superoxide overproduction by the mitochondrial electron-transport chain (Brownlee, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes and high glucose conditions can increase the formation of ROS by multiple biochemical pathways, including glucose auto-oxidation, activation of the polyol pathway which can decrease levels of reduced glutathione and/or increase advanced glycation end products and activation of PKC which activates NAD(P)H oxidase (Fig. 10) (Brownlee, 2001;Brownlee, 2005;Inoguchi et al, 2003a;Inoguchi et al, 2003b;Jain, 2006). All of these events have been suggested to be initiated by superoxide overproduction by the mitochondrial electron-transport chain (Brownlee, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 99%
“…However, while mitochondrial-derived ROS are important for the initiation of oxidative stress responses in models of hyperglycemia, studies in other models indicate that activity of NADPH oxidase is required in order to sustain sufficient levels of ROS formation for the transduction of specific cellular responses (Kimura et al, 2005;Lee et al, 2006b;Schafer et al, 2003). Data showing increased activity of NAD(P)H oxidase in retinas and vascular tissues of diabetic patients and animals and in high glucose-treated endothelial cells suggest that NAD(P)H oxidase is an important source of ROS in the diabetic milieu (Al-Shabrawey et al, In Pressa; Al-Shabrawey et al, In Press-b; Al-Shabrawey et al, 2006;Ellis et al, 1998;Griendling et al, 2000;Inoguchi et al, 2003b;Sonta et al, 2004). Studies using a mouse model for ischemic retinopathy have revealed that superoxide production by NAD(P)H oxidase has a primary role in VEGF expression and retinal neovascularization (Al-Shabrawey et al, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 99%
“…The source of ROS generated during lipotoxicity is controversial. Recent evidence, from a variety of cell types, suggests that processes other than mitochondrial ␤-oxidation, such as NADPH oxidase activity, may be involved (Inoguchi et al, 2003;Quagliaro et al, 2003;Cacicedo et al, 2005).Because oxidative stress is closely linked to ER stress (Oyadomari and Mori, 2004), we hypothesized that eEF1A-1 mediates lipotoxic cell death in response ROS-induced ER stress in cardiomyocytes. Oxidative stress-induced apoptosis requires the release of ER calcium ions (Scorrano et al, 2003), and depletion of these stores can impair normal protein-folding functions, leading to ER stress (Rao et al, 2004;Rutkowski and Kaufman, 2004).…”
mentioning
confidence: 97%
“…In many types of cells, including TAL cells, activation of protein kinase C (PKC) has been shown to stimulate O 2 . production in response to different stimuli, including Ang II (23,24,25). The PKC family of serine/threonine kinases is composed of many isoforms, some of which are expressed in the TAL, including PKC␣, -␤, -␦, -⑀, and - (26,27 the day of the experiment, animals were anesthetized with ketamine (100 mg/kg body weight, intraperitoneally) and xylazine (20 mg/kg body weight, intraperitoneally).…”
mentioning
confidence: 99%